The impact of Gold, Bond, Currency, Metals and Oil markets on the USA stock market - Partalidou, Xanthi; Kiohos, Apostolos; Giannarakis, Grigoris; Sariannidis, Nikolaos (International Journal of Energy Economics and Policy, 2016)
This study examines the impact of financial and economic variables on the industrial Dow Jones Industrial Average (DJIA) using daily data over the sample period March 1995 - May 2014. Gold, Bond, Currency, Metals and Oil market were taken into consideration, and, as well as, their impact on the DJIA. The results of the model GJR – GARCH proved that the purchase of gold, of decade bonds (10 Year Treasury Note) and the U.S. Dollar/Yen exchange rate affect, negatively, the returns of DJIA. On the other hand, it was made clear that the purchase of industrial metals affects, positively, the returns of DJIA. Lastly, our findings indicate that the asymmetry of the oil returns affects- extremely negatively- the DJIA returns. Keywords: GJR-GARCH, Brent oil, Gold, Metals, Equity market, Exchange rates, Bond market, market risk JEL Classifications: C5; G1; G32; R3